Women Prisons in North-Eastern Thailand: How Well Do They Meet International Human Rights Standards? - Srisombat Chokprajakchat; Wanaporn Techagaisiyavanit (International Journal for Crime, Justice and Social Democracy, 2019)
Thailand has one of the highest incarceration rates of women in the world. With an increasing prison population overall as well as an increasing proportion of female inmates, the country faces one of its most challenging tasks in penitentiary administration: reforms to its legal landscape and its correctional practices in line with international standards. A response to such a crisis is to undertake a prison evaluation project to ensure proper implementation of the United Nations Rules for the Treatment of Women Prisoners and Non-custodial Measures for Women Offenders (also known as the ‘Bangkok Rules’). The primary objective of this research article is to assess and identify a prison model that can inspire the development of other prison facilities, while supporting a firm commitment to maintain and improve the status of current model facilities.